2023
DOI: 10.1177/02683555231179548
|View full text |Cite
|
Sign up to set email alerts
|

Leg volume reduction during tiptoe movement is caused by venous ejection and calf muscle contraction

Abstract: Objectives To clarify the cause of leg volume reduction during tiptoe movement in the standing position. Methods The right legs of 20 participants were assessed. The participants performed tiptoe movement in the supine position, and then stood up and performed the tiptoe movement and ankle dorsiflexion. Leg volume changes were recorded continuously using air plethysmography. Results Differences between leg volume changes due to tiptoe movement and the refilling volumes were not significantly different between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Suehiro et al demonstrated that the refilling volume (ejection volume) was larger during dorsiflexion than during the tiptoe exercise, as assessed by air plethysmography, and that ankle dorsiflexion plays a more important role than tiptoe in venous return from the foot and lower leg. 19) The contraction and relaxation patterns of the lower leg muscles during ankle dorsiflexion in the sitting position are similar to those during the swing phase of walking. In this phase, the gastrocnemius venous sinus is empty and under negative pressure, functioning not as a reservoir but as a conduit from the network of intramuscular veins to the axial deep veins.…”
Section: Discussionmentioning
confidence: 74%
“…Suehiro et al demonstrated that the refilling volume (ejection volume) was larger during dorsiflexion than during the tiptoe exercise, as assessed by air plethysmography, and that ankle dorsiflexion plays a more important role than tiptoe in venous return from the foot and lower leg. 19) The contraction and relaxation patterns of the lower leg muscles during ankle dorsiflexion in the sitting position are similar to those during the swing phase of walking. In this phase, the gastrocnemius venous sinus is empty and under negative pressure, functioning not as a reservoir but as a conduit from the network of intramuscular veins to the axial deep veins.…”
Section: Discussionmentioning
confidence: 74%